2018
DOI: 10.1002/admt.201800013
|View full text |Cite
|
Sign up to set email alerts
|

From All‐Printed 2D Patterns to Free‐Standing 3D Structures: Controlled Buckling and Selective Bonding

Abstract: 3D structure into thin cross-sections and fabricate the structure layer-by-layer. [29] This 3D fabrication route relies mainly on metal powders or polymeric materials that are deposited then cooled, crosslinked, or sintered to create the desired 3D structure. [24,29] While these approaches are very successful for expedited prototyping, the resulting printed 3D structures are typically constrained to nonfunctional materials and have limited functionalities that, based primarily on their geometrical shape. [24] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…Here, we present a design strategy to significantly increase the elastic strain energy stored by completely soft robots upon actuation, enabling their rapid and programmable actuation and recovery. Our work finds its foundations in previous approaches to create 3D structures using controlled buckling and selective bonding as a design principle and the work of Cafferty et al, who demonstrated the fabrication of soft grippers using a combination of direct‐ink printing and relaxation of strain. Complimentary to these works, we propose a strategy to exploit elastic energy storage to fabricate a variety of prestressed soft actuators (PSAs) by attaching a flexible but inextensible sheet (paper, textile, or plastic) to a prestressed elastomeric layer.…”
Section: Introductionmentioning
confidence: 93%
“…Here, we present a design strategy to significantly increase the elastic strain energy stored by completely soft robots upon actuation, enabling their rapid and programmable actuation and recovery. Our work finds its foundations in previous approaches to create 3D structures using controlled buckling and selective bonding as a design principle and the work of Cafferty et al, who demonstrated the fabrication of soft grippers using a combination of direct‐ink printing and relaxation of strain. Complimentary to these works, we propose a strategy to exploit elastic energy storage to fabricate a variety of prestressed soft actuators (PSAs) by attaching a flexible but inextensible sheet (paper, textile, or plastic) to a prestressed elastomeric layer.…”
Section: Introductionmentioning
confidence: 93%
“…(iv) It produces structures that can be deformed reversibly by reapplying strain, which can be used to fabricate more complex structures and actuators. This approach differs from prior work, in which strain relaxation formed buckled “pop‐up” structures on flat elastomeric substrates, in that the approach described here allows the entire composite structure, including the substrate, to be fabricated with positive or negative curvature.…”
mentioning
confidence: 99%
“…Buckling instabilities and bending due to compressive in‐plane stresses in 2D sheets may be used to generate 3D shapes . These compressive stresses can result, for example, from swelling of an inhomogeneous hydrogel, or from selective swelling of a homogeneous hydrogel using a mask .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the extreme out‐of‐plane buckling that may take place during stretching, the conductive layer should have commensurate flexibility and conductivity to minimize change in resistance (≈1 Ω) and avoid the formation of permanent damage. Here, an ink formulation, coupling silver flakes and an elastomer binder (Ag‐SIS), described in our previous work, is chosen owing to its superior flexibility and conductivity. Then, the water‐soluble ink is printed to define the free‐standing region of the interconnect.…”
mentioning
confidence: 99%